Toward AI-enabled augmented reality to enhance the safety of highway work zones: Feasibility, requirements, and challenges. (October 2021) - Sabeti, Sepehr; Shoghli, Omidreza; Baharani, Mohammadreza; Tabkhi, Hamed
Abstract: Highway work zones are considered among the most hazardous working environments. In 2018 alone, 124 workers lost their lives to fatal accidents. The lack of predictive safety systems that notify workers of upcoming dangers in advance is a major reason to blame in the highway maintenance and operation community. This article presents an integrative design framework for bringing recent advances in Augmented Reality (AR) and Artificial Intelligence (AI) to enhance the safety of highway workers through real-time multimodal notifications on-spot. To this end, this article conceptualizes and co-designs three major pillars: (1) AR user interface design for multimodal notification, (2) real-time AI at the edge for vehicle detection/classification from distance, and (3) real-time wireless communication in work zone setting to enable latency-aware operation between AI and AR components. Our early results demonstrate that we can achieve 24.83 FPS end-to-end execution latency on the Xavier AGX Jetson board with 48.7% m AP on BDD100K dataset, and a real-time communication covering 120 meters with an average latency of 5.1 ms at the farthest distance. Our mixed-method user research also reveals an acceptable level of excitement and engagement from the body of highway workers toward both the proposed technology and the designed user interface. Overall, this article provides a proof-of-concept toward AI-enabled AR safety systems in highway work zones.